2022
DOI: 10.1161/circresaha.121.319891
|View full text |Cite
|
Sign up to set email alerts
|

Genetic, Molecular, and Cellular Determinants of Sex-Specific Cardiovascular Traits

Abstract: Despite the well-known sex dimorphism in cardiovascular disease traits, the exact genetic, molecular, and cellular underpinnings of these differences are not well understood. A growing body of evidence currently points at the links between cardiovascular disease traits and the genome, epigenome, transcriptome, and metabolome. However, the sex-specific differences in these links remain largely unstudied due to challenges in bioinformatic methods, inadequate statistical power, analytic costs, and paucity of vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 239 publications
1
19
0
Order By: Relevance
“…Because the markers we identified in this study were based on sex-adjusted models such that the markers share similar biology between sex, we did not observe significant sex susceptibility for CAC across the CVHassociated markers. Given the evident sex differences in CVD traits reported in the literature, 64 this topic should be further investigated using a targeted approach, focusing on sex-chromosome methylation and methylation markers in sex hormone receptors and signaling pathways. 65 Similar to genetic risk scores, the MRS allowed us to aggregate relevant epigenetic information that could be clinically meaningful for risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Because the markers we identified in this study were based on sex-adjusted models such that the markers share similar biology between sex, we did not observe significant sex susceptibility for CAC across the CVHassociated markers. Given the evident sex differences in CVD traits reported in the literature, 64 this topic should be further investigated using a targeted approach, focusing on sex-chromosome methylation and methylation markers in sex hormone receptors and signaling pathways. 65 Similar to genetic risk scores, the MRS allowed us to aggregate relevant epigenetic information that could be clinically meaningful for risk stratification.…”
Section: Discussionmentioning
confidence: 99%
“…Greater diversity can even lead to novel insights into disease biology, as a GWAS of coronary artery disease identified ancestry-specific genetic risk loci and an enrichment of genes expressed in the adrenal cortex among Japanese individuals [10]. Similarly, studies should carefully consider sex differences as many diseases exhibit sex-specific differences in rates of disease, which may be partially explained by sex hormones or other biological differences in each sex [127][128][129]. For instance, a study of atherosclerotic plaques found differences in gene regulatory networks across sexes where male samples expressed immune and inflammation genes while female samples expressed genes related to phenotype switching in smooth muscle cells [129].…”
Section: Challenges and Limitations Of Multi-omics Technologiesmentioning
confidence: 99%
“…Other GWAS have found evidence for sexspeci c associations in and visceral fat [46], renal cell carcinoma [47] and longevity [48]. Literature in heterogeneity between sexes and sex-speci c differences in pQTLs are limited [49].…”
Section: Meta-analysismentioning
confidence: 99%